CONTRIBUTION OF CYBER-RELATIONSHIP MOTIVE TO INTERNET ADDICTION IN ADULTS - majorsy, ursa (Universitas Medan Area, 2017)
Nowadays, internet has become a habitual part of human social life, especially for adults. The convenience of internet use lulls adults in cyberspace activity, such as surfing. The great appeal of surfing activity in cyberspace makes addiction to the internet an interesting and bustling phenomenon to be discussed. A psychological factor that closely related to internet addiction is the adultsâ cyber-relationship motive. In this study, cyber-relationship motive is focused on adventure dimension, escape dimension and romance dimension. It aims to determine the social motives behind adult addiction behavior towards the internet. This study used a simple regression of 70 participants with range of age 22-44 years. The result showed that cyber-relationship motive is contributing 31.6% to internet addiction for adults. Further analysis showed that escape dimension of cyber-relationship motive has the most contribution to internet addiction, compared to adventure and romance.